Bacterial tRNA 2′-O-methylation is dynamically regulated under stress conditions and modulates innate immune response - Galvanin, Adeline; Vogt, Lea-Marie; Grober, Antonia; Freund, Isabel; Ayadi, Lilia; Bourguignon-Igel, Valerie; Bessler, Larissa; Jacob, Dominik; Eigenbrod, Tatjana; Marchand, Virginie; Dalpke, Alexander; Helm, Mark; et al. (Nucleic acids research, 2020)
Abstract. RNA modifications are a well-recognized way of gene expression regulation at the post-transcriptional level. Despite the importance of this level of r
Gesehen am 16.02.2021